GAME DIGITAL BERBASIS SMART APPS CREATOR UNTUK MENSTIMULASI KEMAMPUAN BERPIKIR SIMBOLIK ANAK USIA 5-6 TAHUN - Astriani, Dina; Winda Sherly Utami; Akhmad Fikri Rosyadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of digital games based on Smart Apps Creator on the symbolic thinking ability of children aged 5-6 years at TK Mutiara Ibu, Jambi City. The research employed a quantitative approach with a pre-experimental method using a one-group pretest-posttest design. The subjects of this study were 12 children aged 5-6 years in class B1, consisting of 9 girls and 3 boys. Data collection techniques used observation and documentation. The research instrument was an observation sheet based on the Child Development Achievement Level Standards (STPPA) from Permendikbud No. 137 of 2014, covering 10 indicators of symbolic thinking ability. Data analysis techniques included normality test (Shapiro-Wilk), homogeneity test (Levene), hypothesis testing (paired sample t-test), and effect size calculation (Cohen's d). The results showed that the average score of children's symbolic thinking ability increased from 40% in the pretest to 84.2% in the posttest. The paired sample t-test results showed t-count (24.145) > t-table (2.201) with a significance value of 0.000 < 0.05. The effect size calculation using Cohen's d resulted in a value of 6.96, which falls into the very strong category. Thus, it can be concluded that digital games based on Smart Apps Creator have a significant and very strong effect on the symbolic thinking ability of children aged 5-6 years at TK Mutiara Ibu, Jambi City.